1994
DOI: 10.1246/bcsj.67.1701
|View full text |Cite
|
Sign up to set email alerts
|

Practical Preparation of (Z)-2-(5-Amino-1,2,4-thiadiazol-3-yl)-2-methoxyiminoacetic Acid: A Side-Chain of the Fourth Generation of Cephem Antibiotics

Abstract: A Z-isomer (4) of 2-(5-amino-1,2,4-thiadiazol-3-yl)-2-(methoxyimino)acetic acid, which is the common acyl moiety of clinically useful cephem antibiotics, has been prepared from the aminoisoxazoles through the skeletal rearrangement in several routes. Reaction of 3-amino-5-methoxyisoxazole (7) with alkoxycarbonyl isothiocyanates gave methyl 2-(5-alkoxycarbonylamino-1,2,4-thiadiazol-3-yl)acetates (8), which were converted into the target compound 4 through the reaction of the corresponding keto ester with O-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Then, how to efficiently convert compound 13 into 1,2,4-thiadiazoles 15 via a skeleton rearrangement of the thiourea intermediate 14 was one of our main tasks. Initially, treatment of compound 13 with ethoxycarbonyl isothiocyanate under various condition to afford ethyl 3-(2-acetamido-2-oxoethyl)-1,2,4-thiadiazol-5-ylcarbamate ( 15a ) was investigated. , The results in Table reveal that Lewis acids (zinc chloride) or bases (pyridine, triethyl amine, and N , N , N′ , N′ -tetramethylethylenediamine) could not increase the yields of 15a , and the highest yield was 64% under acid- or base-free condition (Table , entry 5). HPLC analysis revealed that the main byproduct was the unrearranged thiourea 14a , and the crude product was purified by recrystallization from acetone to yield a white crystalline.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, how to efficiently convert compound 13 into 1,2,4-thiadiazoles 15 via a skeleton rearrangement of the thiourea intermediate 14 was one of our main tasks. Initially, treatment of compound 13 with ethoxycarbonyl isothiocyanate under various condition to afford ethyl 3-(2-acetamido-2-oxoethyl)-1,2,4-thiadiazol-5-ylcarbamate ( 15a ) was investigated. , The results in Table reveal that Lewis acids (zinc chloride) or bases (pyridine, triethyl amine, and N , N , N′ , N′ -tetramethylethylenediamine) could not increase the yields of 15a , and the highest yield was 64% under acid- or base-free condition (Table , entry 5). HPLC analysis revealed that the main byproduct was the unrearranged thiourea 14a , and the crude product was purified by recrystallization from acetone to yield a white crystalline.…”
Section: Resultsmentioning
confidence: 99%
“…However, there were the two following problems regarding Scheme in the reported method, namely: (1) the overall yield of 2 was low (11% yield); (2) toxic and hazardous agents such as bromine and peracetic acid were used. Alternatively, the key intermediate 6 could be prepared from the 3-amino-5-methoxyisoxaole ( 11 ) directly through the skeletal rearrangement in several routes. , As shown in Scheme , the starting compound 11 was prepared from the malononitrile ( 9 ) through 3,3-dimethoxyacrylonitrile ( 10 ). Reaction of 11 with methoxycarbonyl isothiocyanate afforded 6 in 86% yield.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesis of the thiadiazolyl-oximinoacetic acid side chain is not described in the Medicinal Chemistry patents nor publication, but similar type compounds were published in a 1993 European patent application (Scheme ). The disadvantages of this route include the length (eight linear steps), relatively low overall yield of 12%, and the high temperature (>200 °C) required to convert the trimethoxy nitrile 25 to the vinyl nitrile 26 .…”
Section: Ceftolozanementioning
confidence: 99%
“…We devised a novel and concise preparation directed toward the mass production of the ( Z )-methoxyimino compound: ( Z )-2-(5-amino-1,2,4-thiadiazol-3-yl)-2-(methoxyimino)acetic acid ( 88 ) based on the skeletal rearrangement of the aminoisoxazoles 81 or 84 , and stereoselective formation of 88 (Scheme 8 ). 33 ) 3-Amino-5-methoxyisoxazole ( 81 ) was subjected to the skeletal rearrangement in question. A suspension of methyl chloroformate and KSCN in acetonitrile was stirred at 70°C for 30 min to give methoxycarbonyl isothiocyanate in situ , which in turn reacted with 81 to afford methyl 2-(5-methoxycarbonylamino-1,2,4-thiadiazol-3-yl)acetate ( 83 ) in 86% yield, through skeletal rearrangement of the intermediary thiourea derivative 82 .…”
Section: Syntheses Of the Big Four Antibiotics From Carbohydratesmentioning
confidence: 99%